Diversity of Enforcement Titles in Cross-border Debt Collection in the EU: National Report: Bulgaria - Naydenova, Desislava (University of Maribor Press, 2022)
Applying a systematic approach, this report addressess the main features of enfrocement titles in Bulgaria. It focuses on judgments, court settlements and notarial deeds, scrutinizing their content, form and effects. It conveys theoretical insight into the subject matter as well as conclusions from relevant case law.